(untitled) (Bulletin of criminological association of Ukraine, 2025)
It has been emphasized that the relevance of the issue concerning the concept and features of international legal standards for ensuring human rights and freedoms during the pre-trial investigation stage gains particular importance in the context of modern trends in the development of legal systems, the integration of international norms into national legislation, and the globalization of human rights protection processes. It has been established that in contemporary legal practice, the role of international legal standards is continuously growing, as they serve as the basis for unifying and harmonizing legal activities in the field of criminal justice. It has been clarified that, according to the provisions of several international documents such as the Universal Declaration of Human Rights, the Convention for the Protection of Human Rights and Fundamental Freedoms, and the International Covenant on Civil and Political Rights, special attention is paid to the adherence to the principles of legality, proportionality, and due legal procedure in criminal proceedings. International legal standards for ensuring human rights and freedoms are defined as a set of principles, norms, and recommendations enshrined in international documents. It has been emphasized that the concept of international legal standards for ensuring human rights and freedoms implies their integration into national legislation as the foundation for protecting the constitutional rights of participants in criminal proceedings. It has been argued that the features of these standards are criteria for evaluating procedural actions in terms of respect for human rights, ensuring transparency, and inadmissibility of discrimination. It has been established that the essential features of international legal standards for ensuring human rights and freedoms during the pre-trial investigation stage include: social conditionality; dynamism; systematization; general obligatory nature; universality; implementation of normative and regulatory functions; influence on the legal system of the state; proportionality.